Analysis of Technostress and Its Impact on Lecturer Performance in Technology-Based Learning - Sundari Soekotjo; Dwi Novita Sari; Hardianawati Hardianawati; Indria Sukma Sektiyaningsih; Mintarsih Mintarsih; Pingkan Luciawati Sompi; Rochayati Febriarhamadini; Dina Agnesia Sihombing; Prasastiara Eka Marsella (International Journal of Management Science and Information Technology, 2026)
This study investigates technostress among lecturers in private universities under LLDIKTI Region III Jakarta and examines its impact on lecturer performance in technology-based learning environments. Employing a qualitative case study approach, data were collected through semi-structured in-depth interviews with 15 lecturers from various academic ranks, supported by observation and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings reveal that lecturers experience multiple dimensions of technostress, including techno-overload, techno-invasion, techno-complexity, and psychological strain. Techno-overload emerges as the most dominant form, characterized by increased workload and continuous digital demands. Techno-invasion reflects the erosion of work–life boundaries due to constant digital connectivity, while techno-complexity highlights adaptation challenges to rapidly evolving technologies. These conditions collectively contribute to psychological outcomes such as stress, fatigue, and emotional exhaustion. Although technology enhances instructional flexibility and learning innovation, it simultaneously generates a paradox of increased cognitive and emotional burden. The study further finds that technostress influences lecturer performance in both enabling and constraining ways, depending on individual digital competence and institutional support. Lecturers adopt various adaptive strategies, including peer collaboration, self-directed learning, and participation in training programs, to mitigate technostress. The study concludes that technostress is not merely an individual issue but an organizational phenomenon embedded within digital transformation in higher education. The findings provide implications for developing sustainable digital policies and strengthening institutional support systems to enhance lecturer well-being and performance.